DAMPAK SOSIAL EKONOMI RELOKASI PEDAGANG KAKI LIMA DI KAWASAN SIMPANG LIMA DAN JALAN PAHLAWAN KOTA SEMARANG - Aji Wahyu Heriyanto (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
The aim of this research is to know how much is the socio-economic impacts relocation of street vendors at the intersection of Simpang Lima and Pahlawan streets of Semarang City. This research used inferensial analysis and deskriptif percentase. To know the socio-economic impacts, it was done by interviewing and questionairring some street vendors at the intersec-tion of Simpang Lima and Pahlawan streets of Semarang City. The result of this research showed that the social impact of the relocation of street vendors at the intersection of Sim-pang Lima and a Pahlawan streets of Semarang City a positive impact in terms of the social economy that is improve social relationships among traders, feasibility and convenience of business and can increase the income of street vendors. Still a constraint in terms of infra-structure and facilities faced by street vendors after the relocation government as the manager is expected to be assisted with street vendors rapid response in dealing with the damage to shelter by repairing the damaged parts and providing adequate parking space.